Penerapan Prinsip Good Governance Terhadap Kualitas Pelayanan Publik - Palangda, Listriyanti; Dame, Joubert M (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2020)
This study aims to determine the application of the principles of good governance, the quality of public services, and the effect of applying the principles of good governance on the quality of public services at the Makassar City Land Office. This research is a quantitative descriptive study using incidental sampling techniques. The data was collected by using a questionnaire, conducting interviews, observation, and documentation. The data analysis technique used is descriptive statistical analysis and inferential statistics (product moment correlation test) using the SPSS 18 application. The results of the descriptive analysis show that the application of the principles of good governance and the quality of public services at the Makassar City Land Office belongs to the good category in terms of indicator measuring the variable. The result of the product moment correlation analysis shows that the effect of the application of the principles of good governance governance on the quality of public services is 0.790, which is positive, which means that the level of influence is in the strong category.